Impact of COVID-19 Pandemic on Gastroenterology Fellowship Training in Turkey: A Prospective Nationwide Survey Study - DEMİRTAŞ, COŞKUN ÖZER (AVES, 2021)
Background: The Coronavirus-2019 disease (COVID-19) pandemic has markedly restricted endoscopic and clinical activities in gastroenterology (GI), with a negative impact on trainee education. We aimed to investigate how and to what extent has GI trainees in Turkey are affected by the current pandemic in terms of general, psychological, and educational status. Methods: We conducted a web-based survey sent electronically to 103 official GI trainees in Turkey from 37 centers. The 32-item survey included questions to capture demographic (5-questions), endoscopic (7-questions), personal protective equipment (PPE) (3-questions), psychological and general well-being (11-questions), and educational (6-questions) data. Results: Ninety-six (93.2%) trainees completed the survey, of which 56.3% (n = 54) reported a decrease in independently performed endoscopic procedures. Due to pandemic, 91.7% of standard diagnostic endoscopic procedures, 57.2% of standard therapeutic procedures, and 67.7% of advanced endoscopic procedures were decreased. Out of 96 respondents, we detected signs of anxiety in 88.5%, exposure concern in 92.7%, concerns for prolongation of training period in 49%, loss of concentration and interest in 47.9%, and burnout syndrome in 63.5%. Female gender (odds-ratio: 3.856, 95% confidence interval: 1.221-12.174, P =.021) was the only independently associated factor with pandemic-related anxiety. Conclusions: COVID-19 pandemic has led to high amounts of anxiety and non-negligible rates of burnout syndrome among GI trainees, with a significant reduction in endoscopic activities. More effort and novel strategies are required to deliver sufficient competence and general-psychological well-being to GI trainees.
Keywords: Coronavirus-2019 disease; gastroenterology; fellowship; anxiety; burnout; GASTROINTESTINAL ENDOSCOPY; BURNOUT; ANXIETY; INDIA